PERAN KARANG TARUNA DALAM MEWUJUDKAN SOLIDARITAS PEMUDA DI DESA RANDUSARI KECAMATAN SLOGOHIMO KABUPATEN WONOGIRI - Andhita Risko Faristiana (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2021)
Everyone must have difficulties and problems that must be faced, and indirectly this situation encourages them to help each other and face each other together. This sense of solidarity arises because in every community group there are simultaneously needs, lineage, and the same place to live where they are. However, many young people today are starting to be indifferent to the condition of the environment around them, as if they are becoming individualists and busy with their personal affairs. Based on these problems, this research focuses on the role of youth organizations in realizing youth solidarity in Randusari village. This study aims to determine how the role of youth organizations in realizing solidarity in Randusari Village. The method used is a literature study used by analyzing various sources. This study found that youth organizations in Randusari Village have ways to increase their sense of solidarity such as fostering empathy for others, friendship with others, greeting each other when meeting, and competing for help.